Night and the City - Irwin, Winkler; Niro, Robert De.; Jessica Lange; Cliff Gorman; Alan King; Jack Warden; Eli Wallach; Barry Primus; Gene Kirkwood; Ignazio Spalla; Gerard Murphy; Clem Caserta; et al. (USA Penta Films, 1992)
Robert DeNiro and Jessica Lange are the most impossible couple. He's a failed lawyer. She's a common waitress. Together they get in a downward spiral, as they can't seem to deal with there problems. The lawyer just failed winning a case in court against a famous boxing organiser and he wants revenge by catching the organizer on his own territory: boxing. Although he knows nothing about boxing, with his fine talk he finds the help of a couple of people like the brother of his new enemy. But the relationship with his waitress doesn't make things double as hard.
Harry Fabian is a fast-talking ambulance chaser. He sues and settles, looking to make it big as he carries on an affair with the wife of the owner of his Manhattan cafe hang out. While losing a case to a local mobster who fronts as a sports promoter, Fabian whiffs his future at a boxing gym - he decides to be an impresario. For protection from the mobster, he recruits the boss's older brother as his judge of talent, he books a hall, he orders posters. Soon he's in debt waiting for the big night to rake in the cash. His sweetheart wants to leave her husband, so she needs Fabian's help to get a liquor license. The mobster is making trouble. Can Fabian pull it all off?
Languages: English, Turkish Subtitle: Turkish
Keywords: Crime; Drama